A numerical study of the segregation phenomenon of lognormal particle size distributions in the rotating drum - Yang, Shiliang (2019)
Granular materials are mostly polydisperse, which gives rise to phenomena such as segregation that has no monodisperse counterpart. The discrete element method is applied to simulate lognormal particle size distributions (PSDs) with the same arithmetic mean particle diameter but different PSD widths in a three-dimensional rotating drum operating in the rolling regime. Despite having the same mean particle diameter, as the PSD width of the lognormal PSDs increases, (i) the steady-state mixing index, the total kinetic energy, the ratio of the active region depth to the total bed depth, the mass fraction in the active region, the steady-state active-passive mass-based exchanging rate, and the mean solid residence time (SRT) of the particles in the active region increase, while (ii) the steady-state gyration radius, the streamwise velocity, and the SRT in the passive region decrease. Collectively, these highlight the need for more understanding of the effect of PSD width on the granular flow behavior in the rotating drum operating in the rolling flow regime.